TCR Signal Strength Alters T–DC Activation and Interaction Times and Directs the Outcome of Differentiation - van Panhuys, Nicholas (Frontiers in Immunology, 2016)
The ability of CD4+ T cells to differentiate into effector subsets underpins their ability to shape the immune response and mediate host protection. During T cell receptor induced activation of CD4+ T cells both the quality and quantity of specific activatory peptide/MHC ligands have been shown to control the polarization of naïve CD4+ T cells in addition to co-stimulatory and cytokine based signals. Recently, advances in two photon microscopy and tetramer based cell tracking methods have allowed investigators to greatly extend the study of the role of TCR signaling in effector differentiation under in vivo conditions. In this review we consider data from recent in vivo studies analyzing the role of TCR signal strength in controlling the outcome of CD4+ T cell differentiation and discuss the role of the TCR in controlling the critical nature of CD4+ T cell interactions with dendritic cells during activation. We further propose a model whereby TCR signal strength controls the temporal aspects of T:DC interactions and the implications for this in mediating the downstream signaling events which influence the transcriptional and epigenetic regulation of effector differentiation.